2010
DOI: 10.1103/physrevd.82.083527
|View full text |Cite
|
Sign up to set email alerts
|

Gamma rays from ultracompact minihalos: Potential constraints on the primordial curvature perturbation

Abstract: Ultracompact minihalos (UCMHs) are dense dark matter structures which can form from large density perturbations shortly after matter-radiation equality. If dark matter is in the form of Weakly Interacting Massive Particles (WIMPs), then UCMHs may be detected via their gamma-ray emission. We investigate how the Fermi satellite could constrain the abundance of UCMHs and place limits on the power spectrum of the primordial curvature perturbation. Detection by Fermi would put a lower limit on the UCMH halo fractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…We found that for the mass range 1 GeV-1 TeV, the current abundance of MCHOs which are produced during the e þ e À annihilation phase transition is f MCHOs $ 10 À4 corresponding to the 2 limitation. This is the first constraint using the WMAP data and it is comparable with the results in paper [9], where they used the Fermi gammaray observations.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We found that for the mass range 1 GeV-1 TeV, the current abundance of MCHOs which are produced during the e þ e À annihilation phase transition is f MCHOs $ 10 À4 corresponding to the 2 limitation. This is the first constraint using the WMAP data and it is comparable with the results in paper [9], where they used the Fermi gammaray observations.…”
Section: Discussionsupporting
confidence: 81%
“…N MCHOs is the number density of MCHOs, f MCHOs ¼ MCHOs = critical and this definition is different from [9]. The limitation of the integral is from r cut to R MCHOs .…”
Section: The Effects Of Mchos On Cosmological Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13], the authors discussed the influence of the UCMHs on the cosmic microwave background (CMB) due to the dark matter annihilation within them and obtained the constraints on the abundance of UCMHs. The -ray flux from the UCMHs is also studied by several authors [14][15][16]. Besides the ray, the electrons and positrons can also be produced from the UCMHs due to the dark matter annihilation.…”
Section: Introductionmentioning
confidence: 99%